Connected learning journeys in music production education. Issue 3 (1st December 2018) - Toulson, Rob; Hepworth-Sawyer, Russ
The field of music production education is a challenging one, exploring multiple creative, technical and entrepreneurial disciplines, including music composition, performance electronics, acoustics, musicology, project management and psychology. As a result, students take multiple 'learning journeys' on their pathway towards becoming autonomous learners. This article uniquely evaluates the journey of climbing Bloom's cognitive domain in the field of music production and gives specific examples that validate teaching music production in higher education through multiple, connected ascents of the framework. Owing to the practical nature of music production, Kolb's Experiential Learning Model is also considered as a recurring function that is necessary for climbing Bloom's domain, in order to ensure that learners are equipped for employability and entrepreneurship on graduation. The authors' own experiences of higher education course delivery, design and development are also reflected upon with reference to music production pathways at both the University of Westminster (London, United Kingdom) and York St John University (York, United Kingdom).